CNS inflammatory demyelinating events after COVID-19 vaccines: A case series and systematic review - Rinaldi, Virginia; Bellucci, Gianmarco; Buscarinu, Maria Chiara; Reniè, Roberta; Marrone, Antonio; Nasello, Martina; Zancan, Valeria; Nistri, Riccardo; Palumbo, Roberto; Salerno, Antonio; Salvetti, Marco; Ristori, Giovanni (Frontiers in Neurology, 2022)
Background Vaccinations provided the most effective tool to fight the SARS-CoV-2 pandemic. It is now well established that COVID-19 vaccines are safe for the general population; however, some cases of rare adverse events following immunization have been described, including CNS Inflammatory Demyelinating Events (CIDEs). Although observational studies are showing that these events are rare and vaccines' benefits highly outweigh the risks, collecting and characterizing post-COVID-19 vaccine CIDEs might be relevant to single out potential risk factors and suggest possible underlying mechanisms. Methods Here we describe six CIDEs, including two acute transverse myelitis (ATM), three multiple sclerosis (MS), and one neuromyelitis optica spectrum disorder (NMOSD), occurring between 8 and 35 days from a COVID-19 vaccine. Moreover, we performed a systematic literature search of post-COVID-19 vaccines CIDEs, including ATM, ADEM, MS, and NMOSD/MOGAD, published worldwide between December 2020 and December 2021, during 1 year of the vaccination campaign. Clinical/MRI and CSF/serum characteristics were extracted from reviewed studies and pooled-analyzed. Results Forty-nine studies were included in the systematic review, reporting a total amount of 85 CIDEs. Considering our additional six cases, 91 CIDEs were summarized, including 24 ATM, 11 ADEM, 47 MS, and nine NMOSD/MOGAD. Overall, CIDEs occurred after both mRNA (n = 46), adenoviral-vectored (n = 37), and inactivated vaccines (n = 8). Adenoviral-vectored vaccines accounted for the majority of ADEM (55%) and NMOSD/MOGAD (56%), while mRNA vaccines were more frequent in MS new diagnoses (87%) and relapses (56%). Age was heterogeneous (19–88) and the female sex was prevalent. Time from vaccine to symptoms onset was notably variable: ADEM and NMOSD/MOGAD had a longer median time of onset (12.5 and 10 days) compared to ATM and MS (6 and 7 days) and further timing differences were observed between events following different vaccine types, with ATM and MS after mRNA-vaccines occurring earlier than those following adenoviral-vectored ones. Conclusion Both the prevalence of vaccine types for certain CIDEs and the heterogeneity in time of onset suggest that different mechanisms—with distinct dynamic/kinetic—might underly these events. While epidemiological studies have assessed the safety of COVID-19 vaccines, descriptions and pooled analyses of sporadic cases may still be valuable to gain insights into CIDE's pathophysiology.